Development of the tax administration system in the Republic of Kazakhstan - Ermanova А.А.; Tishtykbayeva А.Zh. (BUKETOV BUSINESS REVIEW, 2019)
In the article the importance of the development of the Institute of tax administration in the fundamental transformation of the tax system is considered. Sufficient development of the tax administration system and the optimization of the work of the tax authorities are the necessary conditions for ensuring the financial security of Kazakhstan. In the article, tax administration is a complex socio-economic and political phenomenon, reflecting the degree of development of market infrastructure, public administration mechanisms and principles of civil society. The activity of the Ministry of Finance of the Republic of Kazakhstan is the main source of information for determining the policy and direction of the country. In the article the indicators used to monitor progress in achieving the country’s goals are discussed and the changes after the reduction and simplification of administrative barriers in the Republic of Kazakhstan is analyzed. The article discusses the forms and methods of tax administration. In conclusion, the authors propose several principles of building a tax system for finding the optimal way of developing and improving tax administration in Kazakhstan.